Integrating Mental Health Perspectives into the Legal Discourse on Reproductive Justice in India. Issue 1 (June 2019) - Parthasarathy, Malavika
The reproductive justice framework envisions a world where all women, including those situated at the intersection of multiple structures of oppression such as class, caste, sexual orientation, disability and mental health, are able to exercise their right to decisional and reproductive autonomy. S. 3(4)(a) of the Medical Termination of Pregnancy Act, 1971, provides that an abortion cannot be performed on a mentally ill woman without the consent of her guardian. I analyse the Indian Supreme Court's decision in Suchita Srivastava v. Chandigarh Administration [(2009) 9 SCC 1] in light of contemporary legal developments in the field of disability law and mental health law. The first argument that I make in this paper is that the Rights of Persons with Disabilities Act, 2016, covers persons with mental illness, with the rights in the Act applicable to those with mental illness as well. The second argument rests on the Mental Healthcare Act, 2017, which recognizes the right to privacy and dignity of mentally ill persons, including their capacity to make decisions affecting healthcare. I argue that the judgment, while path-breaking in its recognition of the reproductive rights of disabled women, is inimical to the rights of mentally ill women, perpetuating dangerous stereotypes about their ability to exercise choices, and dehumanizing them. It is imperative for the reproductive justice framework to inform legal discourse and judicial decision-making, to fully acknowledge the right to self-determination and bodily integrity of mentally ill persons.